Genetic Variant of Glucocorticoid Receptor Gene at rs41423247 and Its Association with Major Depressive Disorder: A Case-Control Study: - Firouzabadi, Negar; Nouraei, Hasti; Mandegary, Ali (Galen Medical Journal, 2018)
Background: Extensive distribution of glucocorticoid receptors (GCRs) in different brain areas along with disruption of hypothalamic-pituitary-adrenal (HPA) axis in major depressive disorder (MDD) and the cross talk between GCRs and HPA proposes genetic variants of GC receptor genes as potential contributors in MDD. Among the GCR polymorphisms, rs41423247, rs6195 and rs6189/rs6190 are suggested to be involved in MDD.Materials and Methods: We investigated the association between rs41423247, rs6195 and rs6189/rs6190 and MDD in a case-control study. One hundred MDD patients along with 100 healthy individuals were enrolled in this study. genetic variants of rs41423247, rs6195 and rs6189/rs6190 were determined in extracted DNAs using PCR-RFLP.Result: The prevalence of heterozygote and mutant carriers of rs41423247 were significantly and by 1.9 fold greater in cases versus controls (P=0.033; OR; 95%CI=1.9; 1.1-3.3). Moreover, carriers of the mutant (G) allele were by 1.8 fold more prevalent in MDD group (P=0.013; OR;95%CI=1.8; 1.1-2.8).Conclusion: Specific carriers of rs41423247 might be more susceptible to developing MDD. This supports the hypothesis of the involvement of GCRs in pathophysiology of MDD. [GMJ.2018;7:e995]